Xylem features detrending methods matter: A case study on earlywood vessels of Fraxinus mandshurica. (November 2021) - Chen, Liuting; Zhu, Liangjun; Liu, Shuguang; Lei, Pifeng; Yuan, Danyang; Li, Zongshan; Wang, Xiaochun
Highlights: Most xylem anatomical features show a clear age-related trend. Not all traditional detrending methods are suitable for xylem features. Detrending methods affect climate signals recorded in xylem features. Abstract: Xylem anatomy can provide valuable information about tree allometry and ecophysiological performance. It has unique advantages in the study of global climate change and forest adaptation compared to traditional ring-width or density proxy parameters. Developing appropriate detrended sequences of xylem features is necessary to carry out a series of further studies. However, the differences between detrending methods and their effects for xylem features are still unclear, presenting a challenge to the choice of proper detrending methods. In this study, we used the earlywood vessel features of Fraxinus mandshurica as an example and compared the differences in four common detrending methods (Spline, CSS: cubic smoothing spline, NEP: negative exponential curve, and RCS: regional curve standardization) to highlight the importance of the detrending methods in dendroanatomical studies. The results show that detrending methods significantly affect the long-term growth trends and climate signals recorded in xylem anatomical features. Among them, NEP has good performance in terms of ring width and vessel number, which is not suitable for other vessel features because of its deterministic nature. Spline and CSS are relatively conservative methods, in which are not easy to make mistakes, but the problem of overfitting (lack of climate signals) deserves attention. Multiple RCS may be a promising detrending method with quantitative wood anatomy technology development if sufficient samples are available. Our results highlight the importance of selecting detrending methods for xylem feature identification and emphasize the importance of testing various detrending methods rather than arbitrarily choosing a standard method. The detrending method should be selected based on the purpose, such as the balance between climate signals and thorough detrended effects. We recommend applying multiple methods to test the growth trends in xylem features before selecting a detrending method. More interdisciplinary studies involving ecophysiology, wood anatomy, and dendrochronology will help to distil the valuable information in xylem features accurately.